2012
DOI: 10.1111/j.1474-9726.2012.00839.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced release and binding of perforin at the immunological synapse underlies the age‐related decline in natural killer cell cytotoxicity

Abstract: SummaryPhysiological aging is accompanied by a marked reduction in natural killer (NK) cell cytotoxicity (NKCC) at the single cell level, but the underlying mechanisms are unknown. To address this issue, we isolated NK cells from healthy young (£ 35 years) and old (£ 60 years) subjects and examined the effect of age on events fundamental to the process of NKCC. Simultaneous assessment of NKCC and NK cell-target cell conjugate formation revealed a marked age-associated decline in NK cell killing but comparable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
120
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(133 citation statements)
references
References 46 publications
8
120
0
1
Order By: Relevance
“…In healthy elderly individuals, the killing, proliferative and response of NK cells to triggering was shown to be reduced [53,54]. More recently, it was shown that the reduced killing may be explained by the altered perforin release and interaction at the immunological synapse site of the target cell [55]. While the formation of the immunological synapse, CD69 expression and intracellular levels of perforin/granzyme B were still comparable in NK cells from young versus elderly individuals, there was a reduced binding of perforin to the target cell membrane.…”
Section: Cancermentioning
confidence: 97%
“…In healthy elderly individuals, the killing, proliferative and response of NK cells to triggering was shown to be reduced [53,54]. More recently, it was shown that the reduced killing may be explained by the altered perforin release and interaction at the immunological synapse site of the target cell [55]. While the formation of the immunological synapse, CD69 expression and intracellular levels of perforin/granzyme B were still comparable in NK cells from young versus elderly individuals, there was a reduced binding of perforin to the target cell membrane.…”
Section: Cancermentioning
confidence: 97%
“…However, not all groups agree with these proposals, with some studies showing no effect for age on perforin expression (Mariani et al, 1996; Hazeldine et al, 2012) and others reporting no difference in NKCC despite marked alterations in receptor expression with age (Almeida-Oliveira et al, 2011). Recently, we showed for the first time that following target cell recognition, NK cells from older adults release less perforin into the immunological synapse when compared to NK cells from their younger counterparts, a defect we attributed to an age-related impairment in the polarisation of lytic granules to the NK target cell interface (Hazeldine et al, 2012). Underlying this impairment appears to be aberrant intracellular signalling proximal to the NK cell membrane as when NK cells are treated with phorbol 12-myristate 13-acetate (PMA) and ionomycin, two agents that bypass cell surface receptors to induce NK cell degranulation, no age-associated difference in perforin release is found (J. Hazeldine, unpublished observations).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent article, Sagiv and co-workers demonstrated that NK-mediated elimination of senescent cells occurs exclusively through the granule exocytosis pathway (Sagiv et al, 2012), a finding that led the group to speculate that an age-related decline in perforin-mediated NKCC may be responsible in part for the increased frequency of senescent cells found in aged tissue (Dimri et al, 1995; Minamino et al, 2002; Price et al, 2002; Sagiv et al, 2012). Recently, we have shown that when compared to those isolated from younger subjects, NK cells from older adults release significantly less perforin into the immunological synapse that is formed following target cell contact (Hazeldine et al, 2012), a defect, which based on the findings of Sagiv et al (2012) would be expected to hamper the ability of NK cells from older adults to remove senescent cells.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of compromised immunity in both younger stressed individuals (Cohen et al 1997;Gallagher et al 2009a, b) and older adults (Arora Duggal et al 2013;Butcher et al , 2001Hazeldine et al 2012;Hazeldine and Lord 2013;Pawelec et al 2005) suggests a potential common mechanism that may be shared between stress and ageing in relation to the immune system. Some forms of immunosuppression seen in response to stressors are also present with age.…”
Section: Ageing Stress and The Immune Systemmentioning
confidence: 99%